Analisis Model SEIRS pada Penderita Diabetes Melitus Tipe-2 menggunakan Metode Runge Kutta Orde-4 - Ahmad Ali Nasution; Hendra Cipta; Rina Widyasari (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by elevated blood glucose levels due to insulin resistance or impaired insulin secretion. Optimal dietary management plays a crucial role in maintaining blood glucose stability. This study analyzes an optimal control model of dietary patterns in the treatment of T2DM using the Runge-Kutta 4th Order (RK4) method. Simulation results show that optimal regulation of calorie intake and glycemic index significantly helps maintain blood glucose levels within the normal range. This study is expected to serve as a reference for medical professionals and nutritionists in designing diet strategies based on mathematical models to enhance the effectiveness of T2DM treatment.